Synthesis and crystal structure of-(10S,13S,16R,Z) −17-ethylidene-16-hydroxy-10,13-dimethylhexadecahydro-3 H-cyclopenta[α]phenanthren-3-one, C21H32O2 - Wei Peng; He Kang; Ye Jiang-Hai; Li Xin-Feng; Zou Juan (Zeitschrift für Kristallographie - New Crystal Structures)
C21H32O2, monoclinic, P21, a = 15.2215(7) Å, b = 7.2235(4) Å, c = 16.3052(7) Å, β = 92.754(4)°, V = 1790.73(15) Å3, Z = 4, Rgt (F) = 0.0503, wRref (F 2) = 0.1345, T = 297(2) K.